Different Effects of Three Selected Lactobacillus Strains in Dextran Sulfate Sodium-Induced Colitis in BALB/c Mice - Cui, Yi; Wei, Hongyun; Lu, Fanggen; Liu, Xiaowei; Liu, Deliang; Gu, Li; Ouyang, Chunhui (PloS one, 2016)
To analyze the changes of different Lactobacillus species in ulcerative colitis patients and to further assess the therapeutic effects of selected Lactobacillus strains on dextran sulfate sodium (DSS)-induced experimental colitis in BALB/c mice. Forty-five active ulcerative colitis (UC) patients and 45 population-based healthy controls were enrolled. Polymerase chain reaction (PCR) amplification and real-time PCR were performed for qualitative and quantitative analyses, respectively, of the Lactobacillus species in UC patients. Three Lactobacillus strains from three species were selected to assess the therapeutic effects on experimental colitis. Sixty 8-week-old BALB/c mice were divided into six groups. The five groups that had received DSS were administered normal saline, mesalazine, L. fermentum CCTCC M206110 strain, L. crispatus CCTCC M206119 strain, or L. plantarum NCIMB8826 strain. We assessed the severity of colitis based on disease activity index (DAI), body weight loss, colon length, and histologic damage. The detection rate of four of the 11 Lactobacillus species decreased significantly (P < 0.05), and the detection rate of two of the 11 Lactobacillus species increased significantly (P < 0.05) in UC patients. Relative quantitative analysis revealed that eight Lactobacillus species declined significantly in UC patients (P < 0.05), while three Lactobacillus species increased significantly (P < 0.05). The CCTCC M206110 treatment group had less weight loss and colon length shortening, lower DAI scores, and lower histologic scores (P < 0.05), while the CCTCC M206119 treatment group had greater weight loss and colon length shortening, higher histologic scores, and more severe inflammatory infiltration (P < 0.05). NCIMB8826 improved weight loss and colon length shortening (P < 0.05) with no significant influence on DAI and histologic damage in the colitis model. Administration of an L. crispatus CCTCC M206119 supplement aggravated DSS-induced colitis. L. fermentum CCTCC M206110 proved to be effective at attenuating DSS-induced colitis. The potential probiotic effect of L. plantarum NCIMB8826 on UC has yet to be assessed.